Biomass and Carbon Stocks in Post-Agriculture Secondary Forest in Manokwari, West Papua, Indonesia - Slamet Arif Susanto; Agatha Cecilia Maturbongs; Heru Joko Budirianto; Eko Tenoyo Sriwidodo; Agustinus Kilmaskossu; Peniwidiyanti Peniwidiyanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Vegetations in post-agriculture forests (PAF) have the potential to absorb carbon dioxide and store it in to the form of biomass. However, information on carbon stocks in post-agriculture secondary forest in Papua, Indonesia still needs to be available. This study aimed to analyze the density of vegetation and its relationship to the carbon stock of aboveground vegetation biomass on PAF in the lowland of Manokwari, West Papua. This study was conducted on PAF aged 4 and 7 years using a one-factor, completely randomized design. Carbon stock is calculated using an allometric equation based on a diameter at breast height of 1.30 m (dbh ≥5cm). The results showed that 60% of the relative density of trees on the two PAF’s was composed by Premna odorata, Piper aduncum, and Macaranga tanarius. Carbon stocks on PAF aged 4 and 7 years reach 550 kg/ha and 140 kg/ha respectively. There is an increase in aboveground biomass and carbon stock with relative tree density and, tree diameter, which is significantly affected by the age of the PAF (P<0,002). The low carbon stock on PAF aged four years indicates that there has been a significant decrease in soil fertility after several years of cultivation by the local Papuan community. Therefore, there must be a difference in land use management between natural secondary forest and post-agriculture forest.